العلاقة بین المخاطر النظامیة وعوائد الأسهم في البورصة دراسة قیاسیة لحالة بورصة الدار البیضاء 2016 -200 - بدیار امینة (Finance and Business Economies Review, 2018)
The objective of this study is to examine the relationship between return and risk and to determine whether there is a systemic risk impact on the shares of the Casablanca Stock Exchange, The study relied on the estimation and testing of the capital asset pricing model based on the historical data of a selected sample of the Casablanca financial market between 2008 and 2016. Using the statistical program spss. The research concluded that there is a statistically significant relationship between the fluctuations in market returns and the fluctuations in the returns of the studied companies, The results of the statistical test also showed that the capital asset pricing model is not valid for use on the Casablanca Stock ExchangeThe study recommended that this study be repeated when the number of companies becomes large, enabling researchers to avoid the impact of irregular risks for each company by creating a diversified portfolio. It also recommended testing other asset pricing models based on various factors such as arbitrage pricing theory), And the multi-factor FAMA model..